Audit expectation gap factors and stakeholders’ confidence in Nigerian quoted firms - Alao, Abdul-Azeez Adeniyi; Olaniyan, Okikijesu Olaide; Jacob, Olumayowa Ayorinde (Journal of Accounting Auditing and Business, 2026)
The Audit Expectation Gap (AEG) has emerged as a demanding concern in the auditing profession, with far-reaching implications for corporate governance, financial reporting, and stakeholder trust; hence, this study investigated the effect of the AEG factors on the stakeholders’ confidence in Nigerian quoted firms. The study employed a cross-sectional survey research design, while a total of one hundred and three (103) valid responses were used for the analysis. The data was analysed via the regression analysis with the aid of the Statistical Packages for the Social Sciences (SPSS) at a 5 per cent level of significance. The findings revealed that only the reliability factor has a significant positive effect on stakeholders’ confidence, while the other factors exhibited an insignificant positive effect on stakeholders’ confidence. The study concluded that the reliability of financial statements plays a crucial role in influencing stakeholders’ confidence in Nigerian quoted firms. Therefore, it was recommended that the Nigerian quoted firms should prioritise accurate, dependable, and timely financial reporting.